2019
DOI: 10.1073/pnas.1909562116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress compromises multicomponent efflux complexes in bacteria

Abstract: Physical forces have a profound effect on growth, morphology, locomotion, and survival of organisms. At the level of individual cells, the role of mechanical forces is well recognized in eukaryotic physiology, but much less is known about prokaryotic organisms. Recent findings suggest an effect of physical forces on bacterial shape, cell division, motility, virulence, and biofilm initiation, but it remains unclear how mechanical forces applied to a bacterium are translated at the molecular level. In Gram-negat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Moreover, there is evidence to suggest that different types of mechanical stress will stimulate different mechanosensitive mechanisms in bacteria. For instance, by applying selective loading modes, Genova, et al [18] demonstrated that octahedral shear stress, in particular, promotes the disassembly of efflux pumps and can render bacteria more susceptible to antimicrobials. Finite element modelling, to resolve the complex stress state of the envelope, could be paired with proteomic analyses, such as those in Genova, et al [18] and Jenkins, et al [13], to better understand the role of mechanical stress in bacteria-nanopattern inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is evidence to suggest that different types of mechanical stress will stimulate different mechanosensitive mechanisms in bacteria. For instance, by applying selective loading modes, Genova, et al [18] demonstrated that octahedral shear stress, in particular, promotes the disassembly of efflux pumps and can render bacteria more susceptible to antimicrobials. Finite element modelling, to resolve the complex stress state of the envelope, could be paired with proteomic analyses, such as those in Genova, et al [18] and Jenkins, et al [13], to better understand the role of mechanical stress in bacteria-nanopattern inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is understood that nanopatterned surfaces kill bacteria by inducing-through contact-mechanical stress and strain in the envelope which exceeds a survivable limit [12,17]. Whether death is the result of only rupture, or also other mechanosensitive physiological effects remains a topic of ongoing study [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Gram-positive pathogenic bacteria produce cell wall-anchored (CWA) surface proteins that are important for the bacteria to colonize the host and promote infections. , The most prevalent CWA proteins are the microbial surface components recognizing adhesive matrix molecules (MSCRAMMs), which are critical in bacterial “adhesion, invasion, and immune evasion.” During colonization and infection, these MSCRAMM-mediated adhesions are subjected to mechanical forces associated with flow stress induced by the dynamic oscillated blood pressure, airflow, and other hydrostatic pressures. The tensile forces applied to a single adhered bacterial cell span over a wide range of magnitude, from the nanonewton (nN) range in the urinary tract needed to withstand the high speed of urinary flow down to piconewton (pN) in capillaries according to the reported shear stress. , …”
Section: Introductionmentioning
confidence: 99%
“…[ 116 ] Compared to cells in soft hydrogels, the cell growth rate decreases in stiff hydrogels with a high Young's modulus. [ 43,116,117 ] The elongation of rod‐shaped microbial cells is inhibited by the hydrogel matrix, although the cells can remain metabolically active ( Figure a, left). [ 116 ] At a higher cell density, the repulsive forces between microbial cells and EPS‐based biopolymers lead to spontaneous cell aggregation in the hydrogels owing to the effect of macromolecular crowding.…”
Section: Influence Of Hydrogels On Living Cellsmentioning
confidence: 99%